2020
DOI: 10.1136/bmjdrc-2020-001520
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness cycle to address transitions in diabetes care during the COVID-19 pandemic and future outbreaks

Abstract: The COVID-19 pandemic is considered a mass casualty incident of the most severe nature leading to unearthed uncertainties around management, prevention, and care. As of July 2020, more than twelve million people have tested positive for COVID-19 globally and more than 500 000 people have died. Patients with diabetes are among the most severely affected during this pandemic. Healthcare systems have made emergent changes to adapt to this public health crisis, including changes in diabetes care. Adaptations in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
2
18
0
1
Order By: Relevance
“…Although the use of existing wearable technologies to generate data is not an absolute requirement, having access to timely and accurate diabetes and other related health data is likely to facilitate better outcomes associated with telehealth. 1 With the current pandemic, there is also a need to maintain optimized glucose management as a protection against poor outcomes associated with COVID-19. 2 Optimal glucose management is more likely to be achieved using telehealth that includes technologies that provide opportunities for data sharing, such as Bluetooth-enabled blood glucose monitoring systems, digital blood pressure measuring devices, electronic scales, personal continuous glucose monitoring (CGM), and potentially, smart insulin pens.…”
Section: Telehealth Is Having a Good Pandemicmentioning
confidence: 99%
“…Although the use of existing wearable technologies to generate data is not an absolute requirement, having access to timely and accurate diabetes and other related health data is likely to facilitate better outcomes associated with telehealth. 1 With the current pandemic, there is also a need to maintain optimized glucose management as a protection against poor outcomes associated with COVID-19. 2 Optimal glucose management is more likely to be achieved using telehealth that includes technologies that provide opportunities for data sharing, such as Bluetooth-enabled blood glucose monitoring systems, digital blood pressure measuring devices, electronic scales, personal continuous glucose monitoring (CGM), and potentially, smart insulin pens.…”
Section: Telehealth Is Having a Good Pandemicmentioning
confidence: 99%
“… General Hyperglycemia without diabetes ICU (n = 13) No ICU (n:47) p ARDS (n = 15) No ARDS (n = 45) p AKI (n = 13) No AKI (n = 47) p ICU (n = 5) No ICU (n = 7) p ARDS (n = 4) No ARDS (n = 8) p AKI (n = 3) No AKI (n = 9) p %TIR, median (IQR) 73 (62–86) 72 (54–89) .68 73 (38–90) 72 (55–85) .95 68 (54–86) 73 (54–90) .77 86 (80–90) 75 (56–95) .56 88 (77–94) 77,5 (64,5–95) .49 73 (68–86) 90 (75–95) .30 %TAR, median (IQR) 18 (6–29) 20 (4–46) .71 18 (6–61) 20 (4–40) .47 23 (12–42) 14 (3–40) .22 6 (0–12) 3 (0–5) .67 9 [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ] 2 (0–4,5) .26 …”
Section: Resultsmentioning
confidence: 99%
“…During the COVID-19 pandemic, critical shortages of personal protective equipment (PPE) has resulted in increasing hospital use of CGM to minimize bedside encounters [ 6 , 7 ]. The result of preliminary studies have indicated that CGM readings correlates well with point of care capillary glucose testing in hospitalized patients with COVID-19, and provides an attractive option to for the management of general medicine and surgery patients with diabetes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite limited guidance, established studies, or widespread support from the clinical community to use CGMs in acute care, 6 some healthcare professionals (HCPs) in the hospital diabetes community have recently begun to prescribe CGMs in the hospital setting for investigational or off-label use for COVID-19 patients. 7 The Continuous Glucose Monitors and Automated Insulin Dosing Systems in the Hospital Consensus Guideline Panel included professionals from a variety of backgrounds. Members included experts in the use of CGMs from adult endocrinology, pediatric endocrinology, obstetrics and gynecology, advanced practice nursing, diabetes care and education, clinical chemistry, bioengineering, and product liability law.…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite limited guidance, established studies, or widespread support from the clinical community to use CGMs in acute care, 6 some healthcare professionals (HCPs) in the hospital diabetes community have recently begun to prescribe CGMs in the hospital setting for investigational or off-label use for COVID-19 patients. 7…”
Section: Introductionmentioning
confidence: 99%